Dry electrical discharge machining: an environmental friendly machining process - Ali, Mohammad Yeakub (2018)
Abstract: The recent ongoing research in dry electrical discharge machining (EDM) is found to be amazing. The established EDM process is capable in fabricating various intricate shapes since it has the ability in removing the material using the thermal energy created by the electrical spark which is carried out in dielectric fluid. Dielectric fluid is significant during the machining operation since it improves the efficiency of the machining process, improves quality of the machined parts, and flushes away the debris from the machining gap. However, the commonly used dielectric fluids are mineral oil-based liquid or hydrocarbon oils have the tendency to cause fire hazard, environmental problems, and health hazard to the machining operators. Therefore, as a solution, dry EDM is introduce as a green machining method where gas with high pressure is used as the dielectric fluid instead of liquid where it act as a coolant and also flushes away the debris from the machining gap. The commonly used gases are atmospheric air, compressed air, liquid nitrogen, oxygen, argon, and helium gas. Lower tool wear, better surface quality, lower residual stresses, thinner white layer, and higher precision in machining are the prime outcome of this dry technique. High accuracy in finish-cut is producible when dry EDM is used since the gap distance between the electrodes are narrower and the reaction force from the gas bubbles during the erosion mechanism is negligible compared to the conventional EDM.